On approximation of averaging operator - Krylovas, Aleksandras (Lietuvos matematikos rinkinys, 2008)
An algorithm for constructing approximations of averaging operators of quasi-periodical functions is presented in the paper. The algorithm can be used for constructinguniformly valid for a long time asymptotical solutions of differential equations with small parameter.
Keywords: averaging; small denominators; perturbation method; differential equations